1961
DOI: 10.3133/pp383a
|View full text |Cite
|
Sign up to set email alerts
|

Storage of ground water behind subsurface dams in the Columbia River basalt, Washington, Oregon, and Idaho

Abstract: Occurrence of ground water in the basalt__________ 2 Suggestions as to general specifications for test wells_ Tectonic deformation of the basalt________________ 3 Test operation of the wells ______________________ _ Tilting and warping_________________________ 3

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
1

Year Published

1979
1979
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 3 publications
0
31
0
1
Order By: Relevance
“…The hydraulic characteristics of layered sequences of basaltic lavas of eastern Washington have been described by many previous investigators, including Newcomb (1959Newcomb ( , 1961Newcomb ( , 1965, Burt (1974), Mac Nish and, and Barker (1979). Their conclusions may be summarized as follows.…”
Section: Primary Basalt (Unit 3)mentioning
confidence: 86%
“…The hydraulic characteristics of layered sequences of basaltic lavas of eastern Washington have been described by many previous investigators, including Newcomb (1959Newcomb ( , 1961Newcomb ( , 1965, Burt (1974), Mac Nish and, and Barker (1979). Their conclusions may be summarized as follows.…”
Section: Primary Basalt (Unit 3)mentioning
confidence: 86%
“…NAS and Piper (1975) speculate that there might be perched water in the Rattlesnake Hills. In the Cold Creek Valley, tight folding dr faulting may account for the high pressures oberved there (Newcomb (1961), as discussed in Brown (1970); Ledgerwood and Deju, 1976).…”
Section: Iv-8 "mentioning
confidence: 98%
“…Creek barrier: Past investigations have shown that "subsurface dams" are found in the Columbia River Basalt [Newcomb, 1961]. The groundwater barriers are the result of faults which are perpendicular to regional groundwater flow.…”
Section: Coldmentioning
confidence: 99%